Adipose Extracellular Matrix/Stromal Vascular Fraction Gel Secretes Angiogenic Factors and Enhances Skin Wound Healing in a Murine Model. (1st August 2017) - Sun, Mingliang; He, Yunfan; Zhou, Tao; Zhang, Pan; Gao, Jianhua; Lu, Feng
Abstract : Mesenchymal stem cells are an attractive cell type for cytotherapy in wound healing. The authors recently developed a novel, adipose-tissue-derived, injectable extracellular matrix/stromal vascular fraction gel (ECM/SVF-gel) for stem cell therapy. This study was designed to assess the therapeutic effects of ECM/SVF-gel on wound healing and potential mechanisms. ECM/SVF-gel was prepared for use in nude mouse excisional wound healing model. An SVF cell suspension and phosphate-buffered saline injection served as the control. The expression levels of vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF), and monocyte chemotactic protein-1 (MCP-1) in ECM/SVF-gel were analyzed at different time points. Angiogenesis (tube formation) assays of ECM/SVF-gel extracts were evaluated, and vessels density in skin was determined. The ECM/SVF-gel extract promoted tube formation in vitro and increased the expression of the angiogenic factors VEGF and bFGF compared with those in the control. The expression of the inflammatory chemoattractant MCP-1 was high in ECM/SVF-gel at the early stage and decreased sharply during the late stage of wound healing. The potent angiogenic effects exerted by ECM/SVF-gel may contribute to the improvement of wound healing, and these effects could be related to the enhanced inflammatory response in ECM/SVF-gel during the early stage of wound healing.